Fiscal federalism in Nigeria: A cluster analysis of revenue allocation to states and local government areas, 1999 - 2008 - Sam O. Olofin; Olusanya E. Olubusoye; Ajide K. Bello; Afees A. Salisu; Akinola S. Olalekan (CBN Journal of Applied Statistics, 2012)
Existing literature on revenue allocation in Nigeria shows more concern for merits and demerits of sharing principles and /or formulae. Several alternatives have been proposed and will continue to be developed to address the unending agitations from beneficiaries. Contrary however, this paper analyzes two items of revenue (statutory and VAT) shared among the states including FCT and all the Local Government Areas (LGAs) between May 1999 and December 2008. The net statutory allocation after deductions was also analyzed. Using Cluster analysis to evaluate revenue allocation in Nigeria, States and LGAs exhibiting similarity in revenue received were grouped and their common features highlighted. The result of this exercise may be a pointer to resolving the issue of viability when combined with other statistics.
Keywords: C38; H71; H77; 330; Cluster Analysis; Revenue Allocation; Fiscal Federalism; Statutory Allocation; VAT